THE EFFECT BETWEEN WORK MOTIVATION AND SELF-EFFICACY ON OCCUPATIONAL WELL-BEING IN PUBLIC ELEMENTARY SCHOOL (SDN) TEACHERS IN PATI DISTRICT - Sumiyati , Siti; Ika Mariyati, Lely (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study investigates the influence of work motivation and self-efficacy on the occupational well-being of public elementary school teachers in Pati District. Method: A quantitative approach was employed, utilizing multiple linear regression analysis on data collected from 203 teachers through an online questionnaire using a 4-point Likert scale. Validated and reliable instruments were used to measure work motivation, self-efficacy, and occupational well-being. Results: The findings indicate that both work motivation and self-efficacy have a significant and positive effect on teachers' occupational well-being. Higher levels of these internal psychological factors are associated with increased well-being, with the combined variables explaining 51.5% of the variance in occupational well-being. Novelty: This study provides a novel contribution by focusing specifically on public elementary school teachers, a group often overlooked in well-being research. It underscores the importance of internal psychological resources in supporting educators’ professional satisfaction and suggests that enhancing motivation and self-efficacy may serve as strategic levers for improving the quality of education in elementary schools.